2019
DOI: 10.1002/14651858.cd009857.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interdental brushing for the prevention and control of periodontal diseases and dental caries in adults

Abstract: Interdental brushing for the prevention and control of periodontal diseases and dental caries in adults (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 85 publications
2
41
2
4
Order By: Relevance
“…However, these high scores are similar to those reported by previous studies. 2,4,6,42 In the present study, it was not observed a significant difference in the number of sites with BOP in BDF + Ib and BDF + Oi groups at T2, as well as an increase in the number of sites with BOP among BDF individuals. Adding to this, data showed that BOP in > 30% of sites was associated with the RP.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…However, these high scores are similar to those reported by previous studies. 2,4,6,42 In the present study, it was not observed a significant difference in the number of sites with BOP in BDF + Ib and BDF + Oi groups at T2, as well as an increase in the number of sites with BOP among BDF individuals. Adding to this, data showed that BOP in > 30% of sites was associated with the RP.…”
Section: Discussioncontrasting
confidence: 62%
“…In general, studies have shown that only manual brushing and dental flossing do not significantly reduce proximal biofilm and gingivitis. 18,20,23,30,[40][41][42] In addition, the effective cleaning of the interdental spaces using toothbrushes is a real challenge. 33 Studies showed better results in reducing PI, gingival index, and BOP with the use of interdental brushes 4,20,21,23,33 and revealed superiority of irrigating devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, a meta‐review was published in which it was concluded that, based on systematic reviews, interdental cleaning with IDB is the most effective method of interdental plaque removal . Upcoming on the market are the GUM Soft‐Picks ® (Sunstar Europe S.A., Etoy, Switzerland).…”
Section: Introductionmentioning
confidence: 99%